Scientific substantiation of health-improving medical application of mineral water with higt content of organic substances at psycho-emotional disorders - Gushcha, S. G. (Journal of Education, Health and Sport, 2015)
Gushcha S. G. Наукове обгрунтування оздоровлюючого лікувального застосування мінеральної води з підвищенним умістом органічних речовин при психоемоційних розладах = Scientific substantiation of health-improving medical application of mineral water with higt content of organic substances at psycho-emotional disorders. Journal of Education, Health and Sport. 2015;5(6):496-502. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.31895 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A496-502 https://pbn.nauka.gov.pl/works/646301 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.04.2015. Revised 05.05.2015. Accepted: 06.06.2015. НАУКОВЕ ОБГРУНТУВАННЯ ОЗДОРОВЛЮЮЧОГО ЛІКУВАЛЬНОГО ЗАСТОСУВАННЯ МІНЕРАЛЬНОЇ ВОДИ З ПІДВИЩЕННИМ УМІСТОМ ОРГАНІЧНИХ РЕЧОВИН ПРИ ПСИХОЕМОЦІЙНИХ РОЗЛАДАХ SCIENTIFIC SUBSTANTIATION OF HEALTH-IMPROVING MEDICAL APPLICATION OF MINERAL WATER WITH HIGT CONTENT OF ORGANIC SUBSTANCES AT PSYCHO-EMOTIONAL DISORDERS С. Г. Гуща S. G. Gushcha Государственное учреждение «Украинский научно-исследовательский институт медицинской реабилитации и курортологи МЗ Украины», Одесса State Institution «Ukrainian Scientific Research Institute of Medical Rehabilitation and Resort Therapy of the Ministry of Health of Ukraine», Odessa Abstract Experimental studies have established a mild calming effect of mineral water with a high content of organic substances "Zbruchanskaya" on the functional state of the central nervous system and the emotional strain of the animals. This character of the biological activity allowed us to determine the direction of further clinical trials. The group of persons with psycho-emotional disorders drank mineral water "Zbruchanskaya" a daily dose of 1% of body weight 3 times a day for 40 minutes before a meal, a course of 21 days. Application of mineral water "Zbruchanskaya" leads to the normalization of psychoemotional condition at 80% of the investigated. At the end of treatment remained only weakly manifestation of psychoemotional disorders. Keywords: functional state of the central nervous system and the emotional strain of experimental animals, correction of psycho-emotional disorders in patients, mineral water "Zbruchanskaya". Реферат Експериментальними дослідженнями встановлено м’який заспокійливий вплив мінеральної води з підвищеним умістом органічних речовин «Збручанська» на функціональний стан центральної нервової системи та емоційну напруженість тварин. Такий характер біологічної активності дозволив визначити напрямок подальших клінічних випробувань. У осіб з психо-емоційними розладами, які вживали мінеральну воду «Збручанська» встановлено нормалізація психоемоційниого стану у 80 % випадків. Наприкінці лікування зберігались лише осточні прояви психоемоційних розладів. Ключові слова: функціональний стан центральної нервової системи та емоційна напруга експериментальних тварин, корекція психоемоційних розладів у хворих, мінеральна вода «Збручанська».